2022
DOI: 10.1111/jfpp.16421
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of quality evaluation method for frozen tilapia ( Oreochromis niloticus ) fillets stored at different temperatures based on fractal dimension

Abstract: To explore an effective quality evaluation system based on microstructure changes, tilapia samples were preserved at the temperature of −20, −40, and −80°C up to a storage period of 270 days. The porous structure of fish muscle was quantified using the cross‐section area (CA) and fractal dimension (FD) of ice crystals, and the effectiveness of the two was compared. The relationships between microstructure changes and traditional quality parameters, including water‐holding capacity, texture properties, K value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Lowering the storage temperature reduces the rate of deterioration in fish. Equally [94,79,93] both observed that a shelf life of 23 weeks was achieved by freezing fish fillets at 20°C, but the thawing process was not investigated in this study. The stiffness of frozen carp fillets decreased due to the freezing process [14], but not due to the storage time.…”
Section: The Trend In Deterioration Levels Of Farmed Fish Under Freez...mentioning
confidence: 95%
See 4 more Smart Citations
“…Lowering the storage temperature reduces the rate of deterioration in fish. Equally [94,79,93] both observed that a shelf life of 23 weeks was achieved by freezing fish fillets at 20°C, but the thawing process was not investigated in this study. The stiffness of frozen carp fillets decreased due to the freezing process [14], but not due to the storage time.…”
Section: The Trend In Deterioration Levels Of Farmed Fish Under Freez...mentioning
confidence: 95%
“…Additionally, [94] and found that temperature changes can also affect rigour contractions in rested and partially exercised Tilapia fillets stored at different temperatures, with higher temperatures leading to faster rigour stages in the muscle. Therefore, it is important to maintain lower temperatures [34].…”
Section: Rigour Mortis Process In Farmed Fishmentioning
confidence: 99%
See 3 more Smart Citations